Teaching Skills for Students in a Practical Teaching Microteaching Course - Kusmiyati, Kusmiyati; Merta, I Wayan (Jurnal Pijar Mipa, 2025)
The Microteaching course trains students to understand basic teaching skills and apply them in teaching practice with fellow students. The purpose of this study was to determine students' explanation skills during teaching practice in the microteaching course. The study was conducted with Biology Education students enrolled in the Microteaching course, class A, during the 2024/2025 academic year. Data were collected using observation sheets during student teaching practice through peer teaching. The instrument used was derived from indicators' explanation skills, with answer choices on a 1-5 Likert scale. The data were analyzed descriptively by calculating the scores obtained by each indicator on the observed explanation skills, then 5 categories were created: very poor, less good, quite good, good, and very good. The results of observations on all observed explanation skills indicators showed that, on average, students were able to apply explanation skills in teaching practice in micro teaching courses with a good category. However, there were still students with very poor and poor presentations, with an emphasis on important points, and feedback indicators. It can be concluded that, on average, students were able to apply explanation skills in teaching practice; however, they still need to continue practising so that, later, when facing school field practice or when becoming real teachers in schools, they become accustomed to using these skills.